Utilizing Technology in Arabic Teaching: Implementation of Media â€œLearning Aljazeera.Netâ€ on Listening Skill Teaching at University of Darussalam Gontor - Rochma, Siti Nikmatul; Mahmudah, Umi; Yahya, Yuangga Kurnia (Arabiyatuna: Jurnal Bahasa Arab, 2021)
This research aimed to get a clear picture of the application of these media in the learning process of Arabic teaching, especially Maharah Istimaâ€™ at the University of Darussalam Gontor. Learning Arabic for non-native speakers requires more variety and innovation, including in the selection of teaching materials, learning methods, and learning media. This is because learning Arabic in Indonesia is an on-going process in search for the ideal form of learning. Researchers used descriptive qualitative research methods with participatory observation data retrieval methods and documents. The researchers used Miles and Hubermanâ€™s technique applied resting upon the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicated that the implementation of learning.aljazeera.net media in listening session rested upon 3 main stages. They were 1) pre-listening which contained vocabulary delivery, 2) the listening process which used videos from the learning.aljazeera.net website which were repeated at least 4 times, and then 3) the post-listening stage, covering the evaluation of listening activities from the simplest form to the most complex form of evaluation. The learning process of listening using the learning.aljazeera.net was a type of intensive, creative, concentrative, and explorative listening activity.